Study of in-hospital outcome in acute myocardial infarction in correlation with thrombolysis in myocardial infarction risk score - Shingade, Pravin; Meshram, Vinay; Madavi, Umesh (International Journal of Research in Medical Sciences, 2019)
Background: The Thrombolysis in Myocardial Infarction (TIMI) risk score is purportedly an integral score for mortality risk prediction in fibrinolysis-eligible patients with STEMI. Attempt was made to evaluate the same by correlating risk stratification by TIMI score with hospital outcome of such patients. Methods: There were 145 cases of STEMI were studied and TIMI risk scores were calculated and analysed vis-à-vis various relevant parameters. The patients were divided into three risk groups: ‘low-risk’, ‘moderate-risk’ and ‘high-risk’ based on their TIMI scores. All patients received routine anti-ischemic therapy and were thrombolysed subsequently, monitored in ICCU and followed during hospital stay for occurrence of post-MI complications. Results: There were 79 patients (54.5%) belonged to low-risk group, 48 (33.1%) to moderate-risk group and 18 (12.4%) to high-risk group according to TIMI risk score. The mortality (total 17 deaths) was observed to be highest in the high-risk group (55.6%), followed by moderate-risk (12.2%) and low-risk group (1.28%) respectively. Out of the 7 potentially suspect variables studied, Killips classification grade 2-4 had the highest relative risk (RR-15.85), followed by systolic BP <100mmHg (RR- 10.48), diabetes mellitus (RR- 2.79) and age >65 years (RR- 2.59). Conclusions: The TIMI risk scoring system seems to be one simple, valid and practical bed side tool in quantitative risk stratification and short-term prognosis prediction in patients with STEMI.